Japanese industry 1963 : the foreign capital research society - The Foreign Capita Research Society; Bank of Japan (Japan The bank of Japan)
Unlike many other books on pornography which concentrate on arguments about restricting or not restricting pornography, this book focuses on the production of adult videos. It outlines and examines the industrial dynamics of the industry, its strategies, technological capabilities and organisational structure. It discusses the socialisation of those who participate in the industry, the role of censorship, the nature of markets and the wider cultural impact of the industry.
Includes indexes.
aia 28/01/2019
Loans
Keywords: Industry - Japan; Japanese industry; Japan